iPSC-derived cerebral organoids reveal mitochondrial, inflammatory and neuronal vulnerabilities in bipolar disorder - Dana El Soufi El Sabbagh; Alencar Kolinski Machado; Lauren Pappis; Erika Leigh Beroncal; Delphine Ji; George Nader; Prathyusha Ravi Chander; Jaehyoung Choi; Angela Duong; Hyunjin Jeong; Bruna Panizzutti; Chiara Cristina Bortolasci; et al. (Translational Psychiatry, 2025)
Abstract Bipolar disorder (BD) is increasingly recognized as a disease with both mitochondrial dysfunction and heightened inflammatory reactivity, yet contribution to neuronal activity remains unclear. To address these gaps, this study utilizes iPSC-derived cerebral organoids (COs) from BD patients and healthy controls to model disease-specific metabolic and inflammatory dysfunction in a more physiologically relevant system. BD COs exhibited mitochondrial impairment, dysregulated metabolic function, and increased nod-leucine rich repeat and pyrin domain containing protein 3 (NLRP3) inflammasome activation sensitivity. Treatment with MCC950, a selective NLRP3 inhibitor, effectively rescued mitochondrial function and reduced inflammatory activation in both BD and control COs. The effect of a Bioactive Flavonoid Extract (BFE), a potential therapeutic, was also explored and yielded a partial rescue of inflammasome activation. These findings highlight a mitochondria-inflammasome axis in BD pathophysiology and establish a novel platform for studying BD-associated cellular mechanisms, ultimately bridging the gap between molecular dysfunction and therapeutic development.